Effects of moisture content and disturbance load on seepage characteristics of weakly consolidated rock mass - Xin, Peihong; Jiang, Jun; Sun, Houwei; Wang, Guoyuan; Li, Xiaoliang; Fan, Wenbo; Li, Xuanli (Frontiers in Earth Science, 2025)
With shallow mineral resources gradually exhausted, deep mineral resource development is critical for national resource security yet faces severe challenges when tunnels cross weakly consolidated rock masses like faults and collapse columns. These rocks are prone to sudden seepage hazards under high stress and water pressure, threatening project safety. To address gaps in existing weakly consolidated rock seepage research—such as traditional theories ignoring dynamic mass loss and unclear “moisture content-disturbance load-permeability” coupling—this study explores permeability evolution mechanisms and quantifies how moisture content and disturbance load affect seepage behavior. Remolded graded gangue samples were prepared; via a THM triaxial seepage apparatus, experiments adjusted moisture content with varying immersion durations and simulated disturbance with three stress paths, monitoring axial strain, flow velocity, particle loss speed and porosity. Results show: Permeation has three stages, the response period from 150 to 180 minutes is critical for water outburst control with permeability increasing over 100 percent compared to the disturbance period. High-moisture samples with around 14 percent moisture have peak particle loss speed 2.2 times that of dry samples with 0 percent moisture. High-disturbance permeability is 1.5 to 2 times that of static loading. The non-Darcy factor rises with moisture content but falls with disturbance, approaching Darcy flow. This study fills prior gaps and supports seepage hazard prevention.